Visualising Eclipses: Graphical Constructions of Eclipse Phenomena in the Sanskrit Astral Sciences - Dhammaloka Jambugahapitiye; Kolachana Aditya; Montelle Clemency (HoST)
Eclipse reckoning constituted a significant component of the Indian astronomical tradition and was underpinned by a sophisticated interplay between mathematical theory, observational data, and visual practices. This paper focuses specifically on the diagrammatic dimensions of eclipse computations as articulated in classical Sanskrit treatises. By closely examining two distinctive passages drawn from the astronomical texts Siddhāntaśekhara and Uparāgakriyākrama, composed over the course of the second millennium CE, we investigate how Indian astronomers employed graphical methods to visually represent eclipse phenomena. These diagrammatic constructions reveal a nuanced understanding of eclipse occurrences. Our analysis highlights key features of these procedures, including the geometric frameworks, instruments, and terminologies employed. We also consider how these visual methods evolved across different texts, noting both similarities and differences in their presentation and underlying rationale. In doing so, we demonstrate how theoretical formulations and empirical observations were integrated within these visual methods, shedding light on how theory and observation informed practice and how these complex astronomical events were made accessible to broader audiences.